PENGARUH IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAHAN, SISTEM INFORMASI AKUNTANSI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Pada SKPD Kota Pekanbaru) - Berry Wan Saputra; Zulbahridar -; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of the implementation of government accounting standards, accounting information systems and internal control systems of the quality of local government financial reports on the regional work units Pekanbaru. The dependent variable used in this study was the quality of local government financial reports. Independent variables used adalahimplementasi government accounting standards, the implementation of information systems akuntansidan implementation of the internal control system. The sample in this research is the head of the financial section and sub regional work units numbered 52 people. Sampling method used in this research is census method. Data collection techniques in this study are primary data, while data analysis technique used is multiple regression analysis were processed with SPSS version 21 for Windows. Results from this study showed that: (1) there are significant implementation of government accounting standards and the implementation of the internal control system of the quality of local government financial reports Pekanbaru, (2) there is no effect of accounting information systems implementation to the quality of local government financial reports Pekanbaru.Keywords: accounting standards, information, control, quality, and financial reports